2022
DOI: 10.3390/ijerph191610407
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturer’s Encroachment and Carbon Emission Reduction Decisions Considering Cap-and-Trade Regulation and Consumers’ Low-Carbon Preference

Abstract: Carbon emission reduction and achieving carbon neutrality has become an inevitable trend in the sustainable development era. We investigate the manufacturer’s encroachment and carbon emission reduction decisions considering government cap-and-trade regulations and consumers’ low-carbon preference. The equilibrium decisions for the four scenarios are analytically obtained and compared based using the Stackelberg game. A comparison with and without cap-and-trade regulation under two encroachment decisions regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Referring to Shen et al [ 46 ] and Ding et al [ 47 ], it is assumed that two classes of participants are risk-neutral and there is no information asymmetry, i.e., both the manufacturers and the government share information.…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…Referring to Shen et al [ 46 ] and Ding et al [ 47 ], it is assumed that two classes of participants are risk-neutral and there is no information asymmetry, i.e., both the manufacturers and the government share information.…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…The scientific contribution of the research is especially important for developed enterprises and countries, which identify their prosperity with a sustainable future and whose resources enable or transform such a transformation in order to achieve greater/faster sustainability. The contribution of the study is also important due to the lack of knowledge about the nature of SD, as was found out [ 111 ], and because different actions that have a positive impact on today’s world become an inevitable trend in the SD era [ 112 ]. Sustainable solutions play a significant role [ 113 ] in contributing to global SD [ 114 ] and must be supported also by theoretical contribution represented by the newly developed model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Effective information updates are more efficient at reducing carbon emissions than promotional allowances. Ding et al [37] investigated manufacturers' decisions on encroachment and carbon emissions reduction, taking into account the carbon trading system and consumers' preferences for low-carbon production. The findings indicated that manufacturers invariably benefited from encroachment decisions if the government opted against cap-and-trade regulations, leading to consistent profit losses for retailers.…”
Section: Customers' Low-carbon Preferencementioning
confidence: 99%